2016
DOI: 10.1590/0104-6632.20160331s20140258
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVE ALKALINE PEROXIDE OXIDATION PRETREATMENT OF SHEA TREE SAWDUST FOR THE PRODUCTION OF BIOFUELS: KINETICS OF DELIGNIFICATION AND ENZYMATIC CONVERSION TO SUGAR AND SUBSEQUENT PRODUCTION OF ETHANOL BY FERMENTATION USING Saccharomyces cerevisiae

Abstract: -Shea tree sawdust delignification kinetic data during alkaline peroxide pretreatment were investigated at temperatures of 120 °C, 135 °C, and 150 °C. The activation energy during delignification was 76.4 kJ/mol and the Arrhenius constant was calculated as 8.4 x 10 6 per min. The reducing sugar yield for the treated to the untreated biomass was about 22-fold. Enzymatic hydrolysis conditions studied were; time (72 h and 96 h), substrate concentration (20, 30, 40, and 50 g/L), and enzyme loadings (10, 25, 40, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Increasing the amount of celluclast and hydrolysis time will be proportional to the increase in the amount of glucose produced. Ayeni et al [20], reported the highest reducing sugar on shea tree sawdust in 4 day hydrolysis time, 50 FPU/g dry biomass, 45 o C, pH 4.8, 40 g/L substrate concentration was 482.40 mg/g dry biomass. In variations of the use of enzymes cellucase SHF process will affect the content of reducing sugar produced, can be seen in graph A, where the variation of cellulase enzymes 20 FPU/g produces (17.423 g/L for 72 h), more reduced sugar content than 10 FPU/g variation (11.423 g/L for 72 h), while the non treatment produced 1.718 g/L for 72 h. To effect substrate amount of raw materials also affect the content of reducing sugar obtained when the hydrolysis process is carried out on raw materials.…”
Section: Correlation Between Reducing Sugar and Ethanol In Shf And Ssmentioning
confidence: 96%
See 1 more Smart Citation
“…Increasing the amount of celluclast and hydrolysis time will be proportional to the increase in the amount of glucose produced. Ayeni et al [20], reported the highest reducing sugar on shea tree sawdust in 4 day hydrolysis time, 50 FPU/g dry biomass, 45 o C, pH 4.8, 40 g/L substrate concentration was 482.40 mg/g dry biomass. In variations of the use of enzymes cellucase SHF process will affect the content of reducing sugar produced, can be seen in graph A, where the variation of cellulase enzymes 20 FPU/g produces (17.423 g/L for 72 h), more reduced sugar content than 10 FPU/g variation (11.423 g/L for 72 h), while the non treatment produced 1.718 g/L for 72 h. To effect substrate amount of raw materials also affect the content of reducing sugar obtained when the hydrolysis process is carried out on raw materials.…”
Section: Correlation Between Reducing Sugar and Ethanol In Shf And Ssmentioning
confidence: 96%
“…The variation of 20 g substrate could produced 19.233 g/L than 10 g substrate was 17.423 g/L and non treatment was obtained 1.718 g/L for 72 h. In this stage of saccharification enzyme, modified cellulose into cellobiose and further into simple sugars such as glucose, saccharification process using enzymes celluclast, enzyme hydrolysis process takes place at pH 4.8 and the temperature of 45-50 o C [21]. From Ganguly et al [22], and Aveni et al [20], the addition of biomass loading and hydrolysis time influences increase in reducing sugar, the maximum substrate loading to produces highest reducing sugar is 7% for 27.78 mg/g while the 40 g/L substrate concentration could produce maximum sugar yield for 42.4%.…”
Section: Correlation Between Reducing Sugar and Ethanol In Shf And Ssmentioning
confidence: 99%
“…The activation energy, in this case, can be defined as the minimum energy that is required by the molecules of pre-treatment solution to initiate delignification. 𝐾 𝐿 can be related to temperature following the Arrhenius law [2]:…”
Section: Delignification Parameters and Kineticsmentioning
confidence: 99%
“…Upstream delignification of biomass is the most crucial and rate limiting step of the whole process of depolymerisation of sugar polymers for obtaining biofuels [2]. There are a number of pre-treatment methods available to delignify biomasses; from the perspective of economy and environment friendliness alkaline peroxide based pre-treatment can be considered the most promising chemical method to delignify a biomass effectively without producing much inhibitors for the following steps of enzymatic hydrolysis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature, the mechanisms for lignin removal from plant biomass bring about size reduction of the substrate, physical redistribution of the components, depolymerization and solubilization [11]. Shea-tree sawdust delignification kinetics has been investigated [12]. The raw material was pretreated at 120-150°C.…”
Section: Introductionmentioning
confidence: 99%